Evaluation of different mechanical recycling methods of EVA foam waste. (November 2021) - Rosa, Vanessa Biondo; Zattera, Ademir José; Poletto, Matheus
In the present work, a proposal for the recycling of ethylene vinyl acetate (EVA) foam waste from the footwear industry using twin-screw extruder was evaluated. Parameters such as antioxidant addition, number of reprocessing, temperature, rotation speed were evaluated. The recycled material was evaluated by means of gel content, scanning electron microscopy (SEM), thermogravimetry (TG) and parallel plate rheometry. From this, the 4 samples were chosen, from the 16 extruded, with a higher probability of forming homogeneous foams to be used in the manufacture of new EVA foams. The foams were evaluated using scanning electron microscopy (SEM), dynamic mechanical analysis (DMA) and physical tests of density, abrasion and permanent compression deformation (PCD). The results showed a decrease in the content of crosslinked gel by up to 13 percentage points for the recycled material with antioxidant. However, there was a possible residual crosslinking, as the crosslinking of all recycled foams was greater than reference (foam). The greatest recycled material homogeneity, observed in the SEM, occurred in the samples processed for five repetitions without antioxidant. Some foams manufactured with recycled waste presented very similar morphological aspects to the reference foam. Foam manufactures with G1 recycled waste (extruded once, at 180°C, 450 rpm, without antioxidant), presented the most uniform and spherical cells. This foam also presented the best responses for the physical tests of PCD and abrasion, even compared to foam without recycle. As well as the lower viscosities for these same samples compared to the previous processing. It was understood that the viscosity of the recycled waste directly interferes with the formation of new EVA foam. Rheometry made it possible to identify the recycling process that resulted in an ideal viscosity material for incorporation in the manufacture of new EVA foams.